1990
DOI: 10.1073/pnas.87.13.5153
|View full text |Cite
|
Sign up to set email alerts
|

Generation of transgenic mice with elevated blood pressure by introduction of the rat renin and angiotensinogen genes.

Abstract: The role of the renin-angiotensin system in blood pressure control and in the development of hypertension was investigated by generating transgenic mice carrying the rat renin or angiotensinogen gene or both genes under the control of the mouse metallothionein I promoter. The systolic blood pressure was significantly elevated in transgenic mice carrying both transgenes but was maintained normally in those bearing either of the transgenes. The transgene was effectively and properly transcribed to form the matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
40
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(42 citation statements)
references
References 16 publications
2
40
0
Order By: Relevance
“…2 Recently, the potential contribution of angiotensinogen in the pathogenesis of hypertension has been suggested by genetic approaches. 2,3 The findings of some studies using transgenic animals and a linkage analysis for the angiotensinogen gene 3,4 also support this hypothesis. Regarding the role of circulating angiotensinogen in the pathogenesis of hypertension, an efficient gene transfer method mediated by a viral liposome complex has been recently used as a delivery system of antisense ODNs in vivo.…”
supporting
confidence: 67%
“…2 Recently, the potential contribution of angiotensinogen in the pathogenesis of hypertension has been suggested by genetic approaches. 2,3 The findings of some studies using transgenic animals and a linkage analysis for the angiotensinogen gene 3,4 also support this hypothesis. Regarding the role of circulating angiotensinogen in the pathogenesis of hypertension, an efficient gene transfer method mediated by a viral liposome complex has been recently used as a delivery system of antisense ODNs in vivo.…”
supporting
confidence: 67%
“…Ohkubo et al (33) previously reported elevated systolic blood pressure in transgenic mice containing both the rat renin and rat angiotensinogen genes. As in our experiments, trans- Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…This permanent hypertension is unusual because of its early development, the absence of aggravation during mouse life, its moderate severity, and its predominance in males. The roles of various genes of the RAS that are potentially involved in the control of BP (renin, angiotensinogen, angiotensin-converting enzyme, and AT 1 genes) has been extensively investigated both by overexpression and by inactivation in mice and rats (20)(21)(22)(23)(24)(25)(26). Inactivation of the Agtr1a gene (27) but not the Agtr1b (7) or the Agtr2 (28, 29) genes, causes a BP decrease, and the duplication of Agtr1a gene results in a moderate increase of BP in female mice (8).…”
Section: Discussionmentioning
confidence: 99%